Improvement of internet portal sites for Mountain villages by the comparison of the sites for rural tourism villages nationwide and overseas [Korean] - Jeon, Jun-Heon; Kim, Jong-Ho; Lee, Kwang-Hee; Lee, Dukjae (2007)
This study aims to compare internet portal sites for rural tourism, and to suggest the improved contents for homepage information on mountain villages under the Korea Forest Service. Design, interface, information source, and communication as estimation indicators were used to understand the characteristics of portal sites, and sub-items under indicators to analyse the portal sites were established. Nationwide portal sites were compared for rural tourism information. Also, German and Italian portal sites were compared as overseas cases. As a result, an internet portal site for information on mountain villages under the Korea Forest Service has to be improved as compared with other portal sites related to rural tourism. Firstly, it is necessary to modify and improve the category explaining mountain villages. Secondly, homepage for developing mountain villages has to be established and linked to potential visitors. Thirdly, portal sites for developing mountain villages subsequently have to be constructed under the site of the Korea Forest Service.